Emerging applications, perspectives, and discoveries in cardiovascular research - Malhotra, Ashim, 1977-; Soni, Shivani, 1975- (Medical Information Science Reference, 2017)
"This book explores the recent findings in the field of cardiovascular sciences and emerging technologies in research, transplant medicine, and organ system biology. The mission of our publication is to highlight the strengths and future potential of this new interdisciplinary approach to cardiovascular science"--Provided by publisher